The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/1879198
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies for Adverse Effects of Antiretroviral Therapy among Adult HIV Patients Attending University of Gondar Referral Hospital, Gondar, Northwest Ethiopia: A Cross-Sectional Study

Abstract: Background Adverse effects from antiretroviral therapy (ART) have an impact on quality of life and medication adherence. There is no clear understanding of how people manage the adverse effects of ART. The individual taking medications which cause serious adverse effects may choose to stop or reduce the medications to relieve the adverse effects. Hence, this study was aimed at assessing coping strategies for adverse effects of ART among adult human immunodeficiency virus (HIV) patients. Methods A cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The majority of respondents were getting emotional and instrumental/informational support, either a medium amount or a little bit. The most commonly used coping strategies were self-distraction, acceptance, and religion, also consistent with previous studies (Deo et al, 2010;Sreelekshmi, 2015;Gelaw et al, 2018;Negi et al, 2019) but contrary to (Anima-Korang et al, 2018). While the least common were substance use, behavioural disengagement, and humour, also evidenced by (Deo et al, 2010;Folayan et al, 2017;Negi et al, 2019).…”
Section: Resultssupporting
confidence: 86%
“…The majority of respondents were getting emotional and instrumental/informational support, either a medium amount or a little bit. The most commonly used coping strategies were self-distraction, acceptance, and religion, also consistent with previous studies (Deo et al, 2010;Sreelekshmi, 2015;Gelaw et al, 2018;Negi et al, 2019) but contrary to (Anima-Korang et al, 2018). While the least common were substance use, behavioural disengagement, and humour, also evidenced by (Deo et al, 2010;Folayan et al, 2017;Negi et al, 2019).…”
Section: Resultssupporting
confidence: 86%
“…At the facility level, as some studies indicate the commonly used solution to avert such problem with the health care provider is reassurance, single drug change and regimen modification [ 29 ]. A study done at Gondar identified that positive emotional, social support seeking, taking other medications, information seeking and non-adherence as a mechanism for coping ART related ADRs by the patients [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, studies showed that toxicity of the drugs is the main causes (58%) for the change of the first-line regimen among HIV patients on antiretroviral therapy, which affects the limited number of our treatment options. It is also one of the primary predictor of poor adherence [25][26][27]. A study conducted in south-west Ethiopia on mortality from adverse drug reaction-related hospitalizations show that 1.5% death.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment knows how is low in the current study, which is inconsistent with a study conducted in Arsi [ 25 ]. Those who accessed the health institution far away (>20 km) from their home were found to more likely to use non-adherence as a coping strategy than those who were nearby (≤20 km), and this variation is might be due to the participants to the current study are using the nearby health centers because the setting is in Addis Ababa and also the study method [ 26 ].…”
Section: Discussionmentioning
confidence: 99%